PHENOMENON OF PLANETARY PERSONALITY: EVOLUTIONARY CONTEXT - Рябека, А. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article views the change of the human image in the context of social development of the planetary community; it states that its division into people of the past, present and future is a completely natural process; modern period is described as contradictory because there are transitional forms of the human-being; the leap to the Planetary and Noospheric forms of being of personality as a predecessor of the emerging radiant mankind is expected.